Manajemen Majelis Adat Aceh Di Kabupaten Bireuen: Peran, Fungsi, Dan Implementasi Dalam Pelestarian Nilai-Nilai Adat - Maisura; Maimun Abdurrahman Amin; Umar Dani (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2026)
The Aceh Customary Council (MAA) is a traditional institution that plays a crucial role in maintaining, preserving, and developing the traditional values ​​of the Acehnese people in accordance with Islamic law. In Bireuen Regency, the MAA plays a strategic role in strengthening cultural identity and maintaining social harmony. This study aims to analyze the management of the MAA in Bireuen Regency, focusing on its role, function, and implementation in preserving traditional values. This research uses a descriptive qualitative approach through literature review and document analysis related to traditional institutions. The analysis is based on management functions, including planning, organizing, implementing, and monitoring. The results indicate that the management of the MAA in Bireuen Regency has been quite effective. In terms of planning, the MAA systematically develops a traditional preservation program. In terms of organization, the MAA coordinates with the local government, traditional leaders, and community organizations. In implementation, various activities, such as customary dispute resolution, socialization of traditional values, and community development, have been carried out sustainably. Meanwhile, the supervisory function is carried out to ensure that the implementation of customary practices remains in accordance with Islamic law and social norms. However, several challenges remain, such as limited human resources, minimal budget support, and the influence of globalization on the younger generation. Therefore, institutional strengthening and program innovation are needed to ensure that customary preservation remains relevant in the modern era.